Impact of Constitutional Court Decision Number 78/PUU-XXI/2023 on Criminal Defamation or Insult in Indonesia - Siburian, Panusunan; Ali Masyhar Mursid; Cahya Wulandari (Law Research Review Quarterly, 2024)
Freedom of opinion is the right of every individual from birth which has been guaranteed by the constitution, In interaction in society it is undeniable that there are always things that cause problems and one of them is insult or defamation. The regulation of defamation in the criminal law system in Indonesia has been regulated in Articles 310-320 of the Criminal Code. In Article 310 paragraph (1) and paragraph (2) a person will be considered guilty of committing a criminal offense of insult or defamation according to the Criminal Code, Law Number 1 of 1946 concerning the Regulation of Criminal Acts, and Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions, On September 4, 2023 the petitioner in this case Haris Azhar, Fatiah Maulidiyanti and the Indonesian Legal Aid Foundation (YLBHI) filed a lawsuit with the Constitutional Court to examine Law Number 1 of 1946 concerning Criminal Law Regulations, the Criminal Code, and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions to the Constitution of the Republic of Indonesia Year 1945,  The impact of the Constitutional Court decision Number 78/PUU-XXI/2023 on the criminal act of insult or defamation in Indonesia finally 14 or article 15 of Law Number 1 of 1946 was declared unconstitutional and non-binding, then the regulation of defamation or insult all became absolute complaint offenses.